Characterization of a fiber optic gyroscope in a measurement while drilling system with the dynamic Allan variance. (November 2015) - Wang, Lu; Zhang, Chunxi; Lin, Tie; Li, Xianmu; Wang, Tao
Abstract : Graphical abstract: Highlights: The validation of the DAVAR for nonstationary noise is discussed. The instantaneous stability of FOGs in a MWD system is described by the DAVAR. The different types of noise in the measured FOG are characterized in a 2D diagram. We analyze the performances of FOGs from an original perspective. The proposal method DAVAR could give us the sound advice to improve the FOG. Abstract: The environment influences Fiber Optic Gyroscopes (FOG) directly. Thus, FOGs in Measurement While Drilling (MWD) system exhibit a non-stationary behavior over time due to strong vibration, high-speed rotation and temperature increasing. Therefore, it is important to introduce a representation that can take the time-varying nature of FOGs' stability into account. The Allan variance is a common and standard method to analyze FOGs, but it cannot be used to analyze the dynamic characteristics. In this effort, a method based on the dynamic Allan variance (DAVAR) was developed. Firstly, the validity of DAVAR was verified by simulated data. Secondly, the FOG working in the harsh environment was characterized by the DAVAR. According to the results, an improved experiment was implemented to verify the practical application of the DAVAR. In addition, a 2-D diagram is used for the first time to illustrate the noise characteristics of FOGs. A 2-D analysis diagram can not only separate and distinguish the stochastic noise term, but also track and reveal the changes in the behavior of FOGs in a clear and intuitive manner. In conclusion, with the new method developed by this paper, the performance of FOGs can be evaluated more comprehensively and effectively.